Computer modeling to optimize the sensitivity of an optical DNA nanosensor - Hushiarian, Roozbeh; Yusof, Nor Azah; Houshiarian, Negin; Abdullah, Abdul Halim; Alang Ahmad, Shahrul Ainliah (Elsevier, 2015)
This paper describes how the sensitivity of an optical DNA nanosensor based on MNPs and QDs was enhanced by using computer simulations including an innovative software, Grasshopper. The data used was derived from a previously constructed mechanism which, although successful in detecting target DNA qualitatively, raised some areas for further investigation.